Prevalence of mild cognitive impairment among former elite athletes without a history of sport-related concussions compared to the general older population: a protocol for a cross-sectional study with exploratory subgroup analyses - Jingjing Ren; Qing Zhao; Haojie Li; Shuo Luan; Jiahui Cong; Hanzhi He; Jiaying Xu; Jinghua Qian (BMJ Open)
Introduction Epidemiological evidence regarding the impact of elite athletic careers on cognitive trajectories remains contentious. Although consistent physical activity has been associated with long-term brain health, former elite athletes appear to represent a unique population. While past research has established a connection between sport-related concussions (SRCs) and later cognitive decline, less attention has been given to the cognitive function of former athletes who have not experienced SRCs. Therefore, well-structured cross-sectional studies accounting for established dementia risk factors are needed to compare mild cognitive impairment (MCI) prevalence between former elite athletes and the general population.Methods and analysis This cross-sectional study will be conducted at Beijing Sport University (BSU) in Beijing, China. It is designed as a comparative study, aiming to recruit a sample of around 360 participants aged 65 and above. This sample will comprise 180 former elite athletes without a history of SRCs recruited via the BSU Retirement Welfare Office (the former athlete group), and 180 age-matched individuals from the communities in three districts in Beijing (the comparison group). Participants will complete a comprehensive questionnaire covering sociodemographic information, dementia-related risk factors, current physical activity levels and, for the former athlete group specifically, details of their athletic careers. MCI and instrumental activities of daily living will be assessed using the Montreal Cognitive Assessment, Memtrax continuous recognition test and Lawton Instrumental Activities of Daily Living (IADL) scale. The primary objective is to determine whether former elite athletes without a history of SRCs have a lower MCI prevalence than the general population. The secondary objective is to assess if these former elite athletes have a reduced prevalence of amnestic MCI and impairment in IADL compared with the general population. Additionally, the study aims to explore whether specific career-related characteristics of former athletes, such as the type of sport and contact exposure, are correlated with their cognitive function and IADL abilities in later life as a secondary exploratory component. The study will calculate the crude prevalence ratios (PRs) and adjusted prevalence ratios (aPRs) with 95% CIs using the modified Poisson regression model with robust error variance.Ethics and dissemination Ethical approval was obtained from the Ethics Committee/Internal Review Board of BSU (approval number: 2024042H). All procedures will adhere to the Helsinki Declaration. The study’s findings will be provided to participants as deemed appropriate. The outcomes will be communicated through abstract presentations at national or international conferences/academic seminars, as well as through publication in a peer-reviewed journal.Trial registration number ChiCTR2400085800.